Evaluation of Direct-Acting Oral Anticoagulant Use in Patients With Cancer. (October 2018) - Davis, Daphne O.; Davis, Kyle A.
Purpose: To evaluate the use of direct-acting oral anticoagulants in patients with cancer and venous thromboembolism (VTE) treated at Ochsner Medical Center with the intent of determining the efficacy and safety of these agents. Methods: Patients were identified by a retrospective data extraction of patients treated at Ochsner Medical Center from January 1, 2013, through December 31, 2015. Patients were included for review if they were ≥18 years of age, with a confirmed diagnosis of VTE and active or history of cancer, and if they received dabigatran, apixaban, rivaroxaban, or edoxaban for at least 6 months. The primary objectives were the rate of recurrence of VTE and the incidence of bleeding at 6 months. Results: Thirty-seven patients were identified. Twelve patients were diagnosed with PE, 21 with DVT, 3 with DVT and PE, and 1 with DVT and superficial vein thrombosis (SVT). Apixaban was used most often (n = 27). No patients experienced a recurrent DVT or PE at 6 months. Two patients experienced adverse effects during treatment. Conclusions: In this single-center, retrospective, observational study in patients with cancer receiving DOAC therapy, there were no episodes of recurrent VTE and only 2 episodes of clinically significant bleeding.